Predictors of False Negatives in Self-Report Screening for Prenatal Substance Use [34R]. (May 2018) - Blake-Lamb, Tiffany; Ondersma, Steven; Chang, Grace; Gilstad-Hayden, Kathryn; Yonkers, Kimberly
Abstract : INTRODUCTION: Substance use during pregnancy has known harmful effects for both the mother and fetus. Few substance use screening tools have been evaluated in pregnancy and only one has been validated against a biochemical assay. The current study sought to examine predictors of false negative screens using the most sensitive of five tested screeners. METHODS: In 2016-2017, women age 18 and over were recruited during prenatal care at three demographically diverse sites. Four existing substance use screeners with published evidence in pregnancy (SURP-P, CRAFFT, WIDUS, and 5Ps), plus the NIDA Quick Screen, were administered to pregnant women in counterbalanced order and followed by collection of urine that was tested for evidence of alcohol, tobacco, marijuana, opiates, cocaine, benzodiazepines, barbiturates, and amphetamines. RESULTS: Among 1, 220 participating women, 397 (32.5%) had evidence of substance use per urine toxicology or self-report, with the SURP-P having the highest sensitivity (85%) but the lowest specificity (37%) for detecting use. Among women with evidence of substance use by urine toxicology or self-report, the odds of screening negative (false negative) on the SURP-P were higher for women with multiparity, lower educational attainment, Hispanic ethnicity, and those receiving public assistance. CONCLUSION: Substance use screening tools with relatively high detection rates during pregnancy may still miss use among clinically important groups of women. This is particularly true among multiparous and low-SES women who may have reason to under-report. Policies allowing safe disclosure to medical providers are desperately needed.